Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae) - Murdy, Edward O.; Ferraris, Jr., Carl J. (Zootaxa, 2003)
A new genus and species of worm goby, Gymnoamblyopus novaeguineae, is described on the basis of a single specimen from the Fly River, Papua New Guinea. It differs from all other amblyopine gobies by the following combination of characters: only one anal-fin pterygiophore anterior to first hemal spine; no Y-shaped second anal-fin pterygiophore; no chin barbels; no scales; no raised dermal folds or ridges; pleural ribs short and posteriorly directed; and mouth vertical. This new taxon is figured and a key to the “Taenioides” group of the Amblyopinae is provided.